Corporate focus and stock returns : evidence from M & A - Chua, Seow Kee (2008)
This project examines both the short-run and long-run wealth effects associated with corporate diversification strategies through analyses of both focus-preserving/increasing and focus-decreasing bidder frims that engage in mergers and acquisitions.